Transportation of sediment carried during flood events in a small urban catchment - Adam Krajewski; Jacek Gładecki; Kazimierz Banasik (Acta Scientiarum Polonorum. Formatio Circumiectus)
The aim of this study is to present results of investigations into rainfall–runoff–suspended sediment transport process, based on field measurements conducted in small (A = 28.7 km2) urban catchment of Służew Creek, located in Warsaw. Hydrological monitoring was carried out by the Department of Hydraulic Engineering at the WULS-SGGW (Warsaw University of Life Sciences). Between 2014–2017, twelve flood events were recorded, during which rainfall, discharge, turbidity, and suspended sediment concentrations were measured. The correlation between the flows and sediment concentration was analysed and dextrorotary hysteresis for all events was indicated, meaning that sediment concentrations during the increase of water flows were higher than at the same flow values during the fall of the flood wave. Also first flush effect has been noted, that is, most of the sediment loads was washed-off at the beginning of the flood event; whereas the peak concentration occurred prior to the maximum discharge. Statistically significant correlation between direct runoff and suspended sediment has been established.